A novel sulfated mannan-carboxymethyl-5-fluorouracil-folic acid conjugates for targeted anticancer drug delivery. (15th March 2023) - Ma, Nan; Kwon, Mi-Hye; Palanisamy, Subramanian; Ge, Yunfei; Zhang, Yutong; Kou, Fang; Dae-Hee, Lee; Lee, Dong-Jin; Shin, Il-Shik; You, SangGuan
Abstract: CFP2 is a sulfated polysaccharide isolated from Codium fragile that shows excellent immunomodulatory activity. To reduce the side effects of 5-fluorouracil (5-FU), CFP2 was used as a macromolecular carrier to react with carboxymethyl-5-fluorouracil (C-5-FU) to form CFP2 -C-5-FU, which further reacted with folic acid (FA) via an ester bond to form novel conjugates (CFP2 -C-5-FU-FA). CFP2 -C-5-FU-FA was confirmed by nuclear magnetic resonance (NMR) analysis. In vitro drug release results showed that the cumulative release rate of C-5-FU was 49.9% in phosphate buffer (pH 7.4) after 96 h, which was much higher than that of the other groups, indicating that CFP2-C-5-FU-FA showed controlled drug release behavior. CFP2 -C-5-FU-FA also exhibited enhanced apoptosis and cellular uptake in vitro . Further, intravenous administration of CFP2 -C-5-FU-FA in an HCT-116 cell-bearing xenograft mouse showed that the conjugates were safe and effective drug delivery systems. These results suggest that folate-targeted conjugates can be used effectively for efficient chemotherapy of colorectal cancer. Graphical abstract: Unlabelled Image Highlights: Sulfated polysaccharides (CFP2) was extracted from Codium fragile . A novel conjugates (CFP2-C-5-FU-FA) was prepared through esterification reaction. CFP2-C-5-FU-FA showed controlled drug release behavior in in vitro . CFP2-C-5-FU-FA exhibited enhanced apoptosis and cellular uptake. Anti-tumor studies performed in vivo using HCT-116 xenograft mice model.